Genome-wide comparative and phylogenetic analysis of putative algal carbohydrate sulfotransferases - Ho, Chai Ling; Low, Xuan Zi; Lee, Wei Kang; Bothwell, John H. (Springer, 2026)
Carbohydrate sulfotransferases (CHSTs) play a vital role in the production of sulfated polysaccharides (SPs) in algae by catalyzing the sulfation of carbohydrate moieties through the transfer of a sulfuryl group from the donor, 3’-phosphoadenosine 5’-phosphosulfate (PAPS). In the present study, putative algal CHSTs with a PF00685, PF03567. PF06990 and PF13469 domain were identified by HMMER search and Protein Basic Local Alignment Search Tool (BLAST) using the well-characterized human CHSTs as queries. Approximately half of the algal CHSTs that contained a PF00685 domain also possessed a PF13469 domain in an overlapping region. These CHSTs were structurally and phylogenetically distinct from algal CHSTs containing PF03567 or/and PF06990 domains. The PF00685/PF13469 domain is commonly found in Chlorophyta, while PF03567 and PF06990 domains are more prevalent in red algae and brown algae, respectively, reflecting the different types of SPs produced by these distinct phyla. Our phylogenetic analyses of algal CHSTs support the hypothesis of a polyphyletic origin, suggesting complex evolutionary histories involving both lineage-specific evolution and significant horizontal gene transfer (HGT) events between algae and organisms from other diverse taxa, including bacteria. In addition, the specificities of algal CHSTs for different carbohydrate moieties and site-specific sulfation patterns were inferred from the phylogenies of human CHSTs and the CHSTs from of algae with known SPs and chemical structures. This approach helps us to bridge the gap in knowledge, as a limited number of algal CHSTs have been biochemically characterized experimentally.